Determination of damaging SNP’s in SHANK3 gene with in silico methods - İrem Gülfem Albayrak; Şeyma Yektar; Süeda Kaya (Egyptian Journal of Medical Human Genetics)
Abstract Background Asperger's syndrome, autism, and other neurodevelopmental diseases are all included under the general term autism spectrum disorder. The SHANK3 gene has a significant role in autism spectrum disorder; mutations in this gene are seen in roughly 1–2% of patients with both autism and intellectual disability. This genetic association provides insight concerning SHANK3's potential significance in the disorder's development. There is considerable evidence associating SHANK3 mutations to autism spectrum disorder; hence, it is worthwhile to investigate the underlying molecular genetic mechanisms of the disease. Results This research uses in silico approaches such as SIFT, PolyPhen-2, I-Mutant 2.0, and Project HOPE to find harmful SNPs, which are the single nucleotide polymorphisms the most prevalent types of genetic variation in humans, in the SHANK3 gene. After the analysis, from the NCBI dbSNP database, 1535 missense SNPs in the SHANK3 gene were identified, with 54 classified as deleterious. Among these, 30 SNPs were confirmed damaging by both SIFT and PolyPhen-2, and 28 led to increased protein stability while two decreased it. In the presented research, effects on protein structure of this SNPs are discussed. Conclusions This in silico study improves our understanding of the complicated molecular changes associated with the SHANK3 gene and contributes to a more comprehensive understanding of the genetic landscape. By deepening our knowledge of the genetic basis and molecular pathways linked to SHANK3 mutations, our findings may offer direction for focused experimental validations and treatment strategies for autism spectrum disorder.